Kajian Tentang Fasilitas Sisi Darat Bandara Ngurah Rai - Ataline Muliasari (Research and Development Agency of The Ministry of Transportation, 2009)
Ngurah Rai Airport, Denpasar can be categorized as a gate economic activity nationally and internationally. This is because the Ngurah Rai Airport, Denpasar, Bali Island which lies an icon of tourism in Indonesia. Most foreign tourists in Indonesia chose Bali as their holiday destination. Traffic density of international flights at Ngurah Rai Airport, of course, needs to be balanced quality of the facilities the land (land side). These needs to be a top prioriy for quality of services and facilities available in the departure terminal and the international arrivals at Ngurah Rai Airport became a general picture of the culture in Bali and tourism traffic in Indonesia, Therefore, the quality of services and facilities at the airport is to note whether it is in Ecordance with The density of the number of passengers coming maupum left. From the results of the analysis showed that some land side facilities for passengers on international flights need to be a development priority by referring to SKEP/77/VI/2005 About Technical Requirements Engineering Facilities Operation Airport.